2016
DOI: 10.1136/gutjnl-2016-312388.99
|View full text |Cite
|
Sign up to set email alerts
|

PTU-012 Faecal Calprotectin as Predictor of Small-Bowel Crohn’s Disease in Capsule Endoscopy – A Systematic Review and Meta-Analysis

Abstract: IntroductionFaecal calprotectin (FC) is a well-established marker of gut inflammation. While the correlation of elevated FC levels with colonic inflammation has been confirmed in several studies,1,2 data regarding the correlation of FC with small-bowel inflammation is either scarce or conflicting.3 Capsule endoscopy (CE) is the modality of choice for detection of small-bowel inflammation and/or small-bowel Crohn’s disease (CD).4 Therefore, we aimed to systematically review and meta-analyse the evidence for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Recent meta-analyses have consistently demonstrated that fecal calprotectin has significant diagnostic accuracy for detecting SB CD 120 121 122 . The likelihood of a positive diagnosis is very low in patients with suspected CD with calprotectin < 50 μg/g.…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…Recent meta-analyses have consistently demonstrated that fecal calprotectin has significant diagnostic accuracy for detecting SB CD 120 121 122 . The likelihood of a positive diagnosis is very low in patients with suspected CD with calprotectin < 50 μg/g.…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…However, our results remained robust even when we restricted our analysis to patients with FCP <50 mcg/g, which has the lowest false negative rate in detecting inflammation in CD. 20 These results suggest that the microbiome changes described here are likely independent from inflammation. Secondly, while these results support an association between microbial changes and persistent symptoms in quiescent CD, we cannot make any firm conclusions on causation here.…”
Section: Discussionmentioning
confidence: 61%
“…We thus repeated our analyses, but only included quiescent CD patients with a FCP <50 mcg/g, which has the lowest false negative rate for active inflammation in CD. 20 Overall, our results were not changed by this lower threshold for FCP. Specifically, Shannon index was significantly decreased in qCD+symptoms compared with qCD-symptoms, IBS-D, and healthy controls…”
Section: Changes In Microbial Diversity In Qcd+symptoms Were Independ...mentioning
confidence: 54%
“…Das Vorliegen intermittierend erhöhter CRP- oder Calprotectin-Werte oder eine Eisenmangelanämie stellen u. a. Warnsymptome dar und können die Entscheidungsfindung unterstützen 63 64 . In einer jüngeren Metaanalyse konnte gezeigt werden, dass bei einem fäkalen Calprotectin-Wert < 50 µg/g das Vorliegen eines Dünndarmbefalls bei M. Crohn sehr unwahrscheinlich ist 65 . Wird eine Videokapselendoskopie bei V. a. M. Crohn durchgeführt, kann eine Patency-Kapsel zum Ausschluss einer relevanten Stenosierung vor Applikation der Videokapsel sinnvoll sein 62 66 , da bei bestehendem M. Crohn Kapsel-Retentionsraten in Metaanalysen mit bis zu 2–3 % angegeben werden 67 .…”
Section: Crohn – Leitlinie Ag 01 Diagnostik Und Initialdiagnostikunclassified